Prenatal exposure to maternal cigarette smoking and structural properties of the human corpus callosum - L. Björnholm; J. Nikkinen; V. Kiviniemi; S. Niemelä; M. Drakesmith; J.C. Evans; G.B. Pike; L. Richer; Z. Pausova; J. Veijola; T. Paus (Academic Press Inc., 2022)
Alterations induced by prenatal exposure to nicotine have been observed in experimental (rodent) studies. While numerous developmental outcomes have been associated with prenatal exposure to maternal cigarette smoking (PEMCS) in humans, the possible relation with brain structure is less clear. Here we sought to elucidate the relation between PEMCS and structural properties of human corpus callosum in adolescence and early adulthood in a total of 1,747 youth. We deployed three community-based cohorts of 446 (age 25–27 years, 46% exposed), 934 (age 12–18 years, 47% exposed) and 367 individuals (age 18–21 years, 9% exposed). A mega-analysis revealed lower mean diffusivity in the callosal segments of exposed males. We speculate that prenatal exposure to maternal cigarette smoking disrupts the early programming of callosal structure and increases the relative portion of small-diameter fibres.